2000
DOI: 10.1006/viro.2000.0328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains of the HPV11 E1 Protein Required for DNA Replication in Vitro

Abstract: The HPV E1 and E2 proteins along with cellular factors, are required for replication of the viral genome. In this study we show that in vitro synthesized HPV11 E1 can support DNA replication in a cell-free system and is able to cooperate with E2 to recruit the host polymerase alpha primase to the HPV origin in vitro. Deletion analysis revealed that the N-terminal 166 amino acids of E1, which encompass a nuclear localization signal and a cyclin E-binding motif, are dispensable for E1-dependent DNA replication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 50 publications
5
51
1
1
Order By: Relevance
“…A similar truncation of HPV33 E1 was reported to be expressed at higher levels than the full-length protein in E. coli (61). Furthermore, we have shown previously that this truncated E1, when made by in vitro translation, retains the ability to support cell-free DNA replication (25). These three E1 proteins were expressed as fusions with an N-terminal 6-histidine tag to facilitate their rapid purification by metal affinity chromatography and hence minimize losses of activity over the course of the procedure.…”
Section: Expression and Purification Of Hpv11 And Hpv6 E1-wesupporting
confidence: 57%
See 4 more Smart Citations
“…A similar truncation of HPV33 E1 was reported to be expressed at higher levels than the full-length protein in E. coli (61). Furthermore, we have shown previously that this truncated E1, when made by in vitro translation, retains the ability to support cell-free DNA replication (25). These three E1 proteins were expressed as fusions with an N-terminal 6-histidine tag to facilitate their rapid purification by metal affinity chromatography and hence minimize losses of activity over the course of the procedure.…”
Section: Expression and Purification Of Hpv11 And Hpv6 E1-wesupporting
confidence: 57%
“…For BPV, it has been demonstrated that ATP hydrolysis is required for displacement of E2 from the origin during assembly of E1 multimeric complexes (17). Either concurrent with or after formation of E1 oligomers, the host polymerase ␣ primase (21)(22)(23)(24)(25) and possibly also replication protein A (22,26) bind to E1, and a replication complex is formed together with additional host factors.…”
Section: From the Department Of Biological Sciences Boehringer Ingelmentioning
confidence: 99%
See 3 more Smart Citations